The Small RNA RyhB Is a Regulator of Cytochrome Expression in Shewanella oneidensis - Meibom, Karin L.; Cabello, Elena M.; Bernier-Latmani, Rizlan (Frontiers in Microbiology, 2018)
Shewanella oneidensis produces an extensive electron transfer network that results in metabolic flexibility. A large number of c-type cytochromes are expressed by S. oneidensis and these function as the fundamental electron transport chain proteins. Although several S. oneidensis cytochromes have been well characterized, little is known about how their expression is regulated. In this study, we investigate the role of the ferric uptake regulator (Fur) and the sRNA RyhB in regulation. Our results demonstrate that loss of Fur leads to diminished growth and an apparent decrease in heme-containing proteins. Remarkably, deleting the Fur-repressed ryhB gene almost completely reverses these physiological changes, indicating that the phenotypes resulting from loss of Fur are (at least partially) dependent on RyhB. RNA sequencing identified a number of possible RyhB repressed genes. A large fraction of these encode c-type cytochromes, among them two of the most abundant periplasmic cytochromes CctA (also known as STC) and ScyA. We show that RyhB destabilizes the mRNA of four of its target genes, cctA, scyA, omp35, and nrfA and this requires the presence of the RNA chaperone Hfq. Iron limitation decreases the expression of the RyhB target genes cctA and scyA and this regulation relies on the presence of both Fur and RyhB. Overall, this study suggests that controlling cytochrome expression is of importance to maintain iron homeostasis and that sRNAs molecules are important players in the regulation of fundamental processes in S. oneidensis MR-1.